Effect of food to microorganisms (F/M) ratio on biohythane production via single-stage dark fermentation. (19th March 2021) - Thi Nguyen, Mai-Linh; Hung, Pang-Chun; Vo, Tan-Phat; Lay, Chyi-How; Lin, Chiu-Yue
Abstract: Hythane is a mixture of hydrogen and methane gases which are generally produced in separate ways. This work studied mesophilic biohythane gas (H2 +CH4 +CO2 ) production in a bioreactor via single-stage dark fermentation. The fermentation was conducted in batch mode using mixed anaerobic microflora and food waste and condensed molasses fermentation soluble to elucidate the effects of food to microorganisms (F/M) ratio (ranging from 0.2 to 38.2) on gas production, metabolite variation, kinetics and biohythane-composition indicator performances. The experimental results indicate that the F/M ratio and fermentation time affect biohythane production efficiency with values of peak maximum hydrogen production rate 9.60 L/L-d, maximum methane production rate 0.72 L/L-d, and hydrogen yield (HY) of 6.17 mol H2 /kg CODadded . Depending on the F/M ratios, the H2, CH4 and CO2 biogas components were 10–60%, 5–20% and 35–70%, respectively. Prospects for the further real application for single-stage biohythane fermentation based on the experimental data are proposed. This work characterizes an important reactor operation factor F/M ratio for innovative single-stage dark fermentation. Graphical abstract: Image 1 Highlights: Biohythane (H2 +CH4 +CO2 ) was produced in a single-stage dark fermentation. F/M ratio and fermentation time affect biohythane production efficiency. H2 component dominated at F/M ratio 7.6 but CH4 was ca. 20% at F/M ratios 0.2–2.0. Peak H2 /(H2 +CH4 ) 1 and H2 /(H2 +CH4 +CO2 ) 0.5 were obtained at high F/M ratio 7.6. Prospects of field applications of the process were elucidated.